Impact of Riverine Pollutants on the Water Quality of Lake Chaohu, China. (March 2019) - Zhang, Wang; Lei, Kun; Yang, Libiao; Lv, Xubo
Abstract: The water environmental capacities for CODMn, TP, and NH3 -N in Lake Chao were estimated with a zero-dimensional model using Class III water quality as the target. The effects of river pollutants transported by the eight major tributaries on the lake's water quality were then analyzed. The results showed that the water environmental capacities for CODMn, TP, and NH3 -N in Lake Chao for 2002-2008 were 6.21-6.74, 0.05-0.06, and 1.01-1.27 × 10 4 ton/yr, respectively. The safety margins for CODMn, TP, and NH3 -N, based on the lake's background reserves, were 5.17-5.86, 0.01-0.03, and 0.89-1.12 × 10 4 ton/yr, respectively. Annually, the river pollutants transported by the tributaries to the lake amounted to 3.58-4.49 × 10 4 ton of CODMn, 0.19-0.27 × 10 4 ton of TP, and 4.09-5.47 × 10 4 ton of NH3 -N. The total amount of CODMn exported by the tributaries was less than the water environmental capacity (accounting for 56-68%) and below the safety margin (accounting for 70-82%) of the lake. However, the total amounts of TP and NH3 -N were 3.78-14.75 times higher than the water environmental capacity and the safety margin of the lake. To prevent further deterioration of the lake's water quality, it is critical to strengthen pollution control in the rivers around the lake and to reduce the sources of river pollution.